Pemberdayaan Nasyiatul Aisyiyah Muhammadiyah melalui Pelatihan Paralegal : Perlindungan Hukum Perempuan dan Anak di Kabupaten Banyumas - Susilo Wardani; Ika Ariani Kartini; Ratna Kartika Wati (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Violence against women and children remains a serious issue in Banyumas Regency, exacerbated by limited legal awareness and inadequate community-based legal assistance capacity. This condition highlights the need for community empowerment through strengthening the role of women’s organizations at the grassroots level. This community service program aims to empower members of Nasyiatul Aisyiyah Muhammadiyah Banyumas through paralegal training to enhance legal understanding and initial legal assistance capacity for women and children. A participatory approach was employed, including material enrichment, group discussions, group dynamics, and role-playing activities. The results indicate an improvement in participants’ understanding of paralegal concepts, women’s and children’s rights, and basic legal procedures for handling cases of violence. Furthermore, the training increased participants’ readiness to act as initial legal companions and strengthened the organizational role of Nasyiatul Aisyiyah as a community-based legal protection actor. This program contributes to expanding access to justice and reinforcing sustainable legal protection for women and children at the community level.